Demographic and Clinical Characteristics of Patients with Sustained and Switching Treatments Using Biological and Targeted Synthetic Disease-Modifying Antirheumatic Drugs: A Multicenter, Observational Cross-Sectional Study for Rheumatoid Arthritis - YAĞCI, İLKER; DURUÖZ, MEHMET TUNCAY (SPRINGER, 2022)
Introduction Rheumatoid arthritis is a chronic inflammatory disease with different disease activity grades. Several registries have been designed to determine the appropriate regimens of disease-modifying antirheumatic drugs to obtain sustained clinical remission. We examined epidemiological and clinical characteristics of rheumatoid arthritis patients using a clinical registry database (BioSTaR) and analyzed the differences in patients with sustained and switched therapies. Methods A multicenter, observational cross-sectional study for rheumatoid arthritis was performed between February 2019 and September 2020 using the BioStaR-RA registry. Demographic and clinical characteristics were prospectively recorded into a specifically designed electronic database. The patients were divided into three groups due to the heterogeneity of the study cohort. Patients were grouped as Group I (Initial; within the first 6 months of treatment with biological/targeted synthetic drugs), Group ST (Sustained Treatment; any first drug lasting for at least 6 months without any change), and Group S (Switch; any switching to another drug). Comparative analysis was performed between sustained treatment (Group ST) and drug switching (Group S) groups. Results The study included a total of 565 patients. The mean age was 53.7 +/- 12.8 years, and the majority were female (80.4%). There were 104, 267, and 194 patients in Groups I, ST, and S, respectively. Erosive arthritis and hematological extra-articular involvement were more frequently detected in Group S than Group ST (p = 0.009 and p = 0.001). The patients in Group S had significantly higher disease activity scores (DAS28-CRP, CDAI, and SDAI) (p = 0.025, p = 0.010, and p = 0.003). There were significantly more patients with moderate disease activity in Group S (p < 0.05). Conclusions The groups with sustained treatment and switching included patients with different disease activity status, although higher disease activity was determined in switchers. Overall, moderate disease activity and remission were the most common disease activity levels. Lower disease activity scores, lower hematologic manifestations, better functional status, and lesser radiographic damage are associated with sustained treatment.
Keywords: Rheumatoid arthritis; Disease-modifying antirheumatic drugs; Registries; Treatment switching; RHEUMATOLOGY/EUROPEAN LEAGUE; AMERICAN-COLLEGE; REMISSION RATES; RISK; MANAGEMENT; THERAPY; SAFETY